Transcription initiation in mycobacteria: a biophysical perspective. Issue 2 (14th March 2020) - Boyaci, Hande; Saecker, Ruth M.; Campbell, Elizabeth A.
ABSTRACT: Recent biophysical studies of mycobacterial transcription have shed new light on this fundamental process in a group of bacteria that includes deadly pathogens such as Mycobacterium tuberculosis ( Mtb), Mycobacterium abscessus ( Mab), Mycobacterium leprae ( Mlp ), as well as the nonpathogenic Mycobacterium smegmatis ( Msm ). Most of the research has focused on Mtb, the causative agent of tuberculosis (TB), which remains one of the top ten causes of death globally. The enzyme RNA polymerase (RNAP) is responsible for all bacterial transcription and is a target for one of the crucial antibiotics used for TB treatment, rifampicin (Rif). Here, we summarize recent biophysical studies of mycobacterial RNAP that have advanced our understanding of the basic process of transcription, have revealed novel paradigms for regulation, and thus have provided critical information required for developing new antibiotics against this deadly disease.